Recurrent Hypertriglyceridemia-Induced Pancreatitis due to Multifactorial Chylomicronemia Syndrome in a Patient With Ketosis-Prone Diabetes Mellitus - Thewjitcharoen Yotsapon; Komindr Surat; Veerasomboonsin Veekij; Wattanawiroon Kewalin; Nakasatien Soontaree; Krittiyawong Sirinate; Himathongkam Thep (Clinical Medicine Insights: Case Reports, 2022)
The triad of diabetic ketoacidosis (DKA), severe hypertriglyceridemia, and acute pancreatitis have been occasionally described in severely obese patients with type 2 diabetes mellitus (T2DM). Herein, we present a long-term clinical course of a Thai man with ketosis-prone diabetes mellitus (KPDM) complicated with recurrent pancreatitis due to multifactorial chylomicronemia syndrome. Genetic testing showed no mutation in lipoprotein lipase (LPL) and its co-factors. The patient was referred to multidisciplinary team for lifelong weight loss consultation, limiting intake of fat and simple carbohydrates, and adherence to lipid-lowering medications. Subsequent follow-up 1 year later showed no recurrent pancreatitis. In patients with multifactorial chylomicronemia syndrome, long-term management with dietary modifications together with pharmacotherapy remains the cornerstone of successful treatment.